PENGARUH KETELADANAN GURU TERHADAP KEDISIPLINAN SISWA KELAS V DI UPT SDN 09 SITIUNG - Aima Nurazila; Ahmad Ilham Asmayadi; Eka Filahamasari (LPPM Universitas Cipta Mandiri, 2025)
This study aims to determine the influence of teacher exemplary behavior on the discipline of fifth grade students at UPT SD Negeri 09 Sitiung. Teacher exemplary behavior is a positive behavior shown by teachers in the form of attitudes, speech, and daily actions that can be role models for students. In the context of elementary education, teacher exemplary behavior is very important because students at elementary school age tend to imitate and emulate what they see from their immediate environment, especially from teachers as authority figures at school. This study uses a quantitative approach with a correlational method, the sample in this study was all fifth grade students at UPT SD Negeri 09 Sitiung, totaling 8 people. The data collection technique used a closed questionnaire, which was compiled based on indicators of teacher exemplary behavior and student discipline. Instrument validation was tested through expert judgment and statistical tests. The results of the data study showed that there was no significant influence between teacher role models on the discipline of fifth grade students at UPT SD Negeri 09 Sitiung. The significance value obtained was greater than 0.05, which means that the hypothesis (H0) was accepted and (Ha) was rejected. This shows that even though teachers have shown exemplary behavior, this does not necessarily affect the level of student discipline. There may be more dominant factors in shaping discipline, such as the family environment, peers, or the school's discipline system.This study concludes that teacher role models are not the only factor that determines student discipline. Therefore, it is recommended that schools and related parties pay attention to other factors that contribute to shaping students' disciplined behavior as a whole.